2015
DOI: 10.1039/c4cc07554d
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a quasi-solid structure by intercalated noble gas atoms in pores of CuI-MFU-4l metal–organic framework

Abstract: The primary adsorption sites for Kr and Xe within the large-pore metal-organic framework Cu(I)-MFU-4l have been investigated by high-resolution synchrotron powder diffraction, revealing an enormous number of adsorption sites: in total, 10 crystallographically different positions for Xe and 8 positions for Kr were localized, the first five of which are located near metal atoms and the organic linker, and the remaining sites form a second adsorption layer in the pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Since noble gases lack chemical reactivity, the only possible mechanism of adsorption for them is Van der Waals interaction based on the polarizability of the atoms. Metal sites are the most polarizable part of the MOF's structure, and thus they are also the main adsorption sites with highest binding energy to adsorbed noble gas atoms, as was confirmed for CPO-27 (present work), MFU-4l, 14,60 and MOF-5. 13 The isosteric heat of adsorption of highly polarizable metal sites can be exceeded only by increased interaction between adsorbed atoms and framework, which might be achieved through the geometrical confinement of adsorbed atoms in small pores, i.e.…”
Section: Discussionsupporting
confidence: 65%
“…Since noble gases lack chemical reactivity, the only possible mechanism of adsorption for them is Van der Waals interaction based on the polarizability of the atoms. Metal sites are the most polarizable part of the MOF's structure, and thus they are also the main adsorption sites with highest binding energy to adsorbed noble gas atoms, as was confirmed for CPO-27 (present work), MFU-4l, 14,60 and MOF-5. 13 The isosteric heat of adsorption of highly polarizable metal sites can be exceeded only by increased interaction between adsorbed atoms and framework, which might be achieved through the geometrical confinement of adsorbed atoms in small pores, i.e.…”
Section: Discussionsupporting
confidence: 65%
“…In other words, it is reasonable to assume that the 3-fold ligand provides a similar steric environment around the Cu­(I) center in both the scorpionate complex and Cu­(I)-MFU-4 l . We note that Magdysyuk et al ascribed the lack of difference between Xe and Kr adsorption in MFU-4 l and Cu­(I)-MFU-4 l to steric effects around the Cu­(I) site. However, our calculations (see the Supporting Information) show that the lack of interaction with the Cu­(I) center is the primary reason for the weak adsorption of these noble gases in these MOFs, which is consistent with the observed and calculated weak Xe binding on Cu surfaces …”
Section: Resultsmentioning
confidence: 56%
“…It was found that the metal cations are connected through organic ligands and hydroxide anions to form an extended two-dimensional metal–organic framework (MOF) structure. MOF compounds, in their crystal structures, combine organic and inorganic building blocks to give hybrid structures with a plethora of interesting properties. …”
Section: Introductionmentioning
confidence: 99%